Silicon Effect and Microstructural Evolution of Hot Dip Galvanized Coating of Structural Steels - Bustos-Castillo, O; Artigas-Abuin, A; Sanchez-Villa, C; Bruna-Rivera, H (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The microstructure of the coating during hot-dip galvanizing under industrial conditions of two structural steels, a low-silicon ASTM A36 steel and a high-silicon Q345B steel, both of commercial grade, have been characterized for industrial-relevant times. In both cases, it is noted that the formation of the Fe–Zn phases begins in the early stages in the heating step of the steel, a situation in which all the phases are in the solid state. These last observations have been taken into consideration and the microstructures of short times are analyzed, showing that the effect of silicon is present at longer times. The characterization was carried out through traditional metallographic techniques including SEM-EDS and XRD equipment. The evolution in time of the microstructure of both steels is examined, being able to observe that the mechanism by which silicon accelerates the formation of Fe–Zn phases in galvanizing is related to the presence of the liquid phase in contact with the ζ layer formed in earlier times, accumulating silicon in the ζ–liquid interphase. These results are directing the analysis towards proposing the hypothesis of a mechanism of penetration of the liquid phase through ζ–ζ boundaries by variations in the surface free energies that allow the penetration of the liquid phase according to the Gibbs Smith condition. Finally, the observations provided us with a deeper understanding of the phase evolution in the hot-dip galvanizing of high silicon steels. © 2023 by the authors.